CO2 emissions and bank stability – evidence from Southeast Asia countries - Oanh, Vu Thi Kim; Cuong, Ta Viet; Anh, Nguyen Ha Vy; Duong, Hoang Nhat (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of CO₂ emissions on the financial stability of commercial banks in Southeast Asia, measured by the Z-score. Recognizing climate change as a systemic threat, the research highlights how climate change can erode banks’ stability. Using panel data from 22 banks across Malaysia, the Philippines, Thailand, and Indonesia during 2012–2023, the study employs robust econometric models, including system GMM, to capture dynamic and nonlinear effects. The findings reveal a significant U-shaped relationship between CO₂ emissions and banking stability: higher CO₂ emissions initially decrease bank stability, but beyond a certain threshold, further increases in emissions positively affect stability, possibly due to enhanced regulatory frameworks, technological innovation, and improved risk management associated with the transition to a low-carbon economy. The study also sheds light on the impact of bank-related variables such as bank size, leverage, and loan-to-deposit ratio, as well as macroeconomic variables like GDP and CPI on bank stability. This research contributes empirical evidence on climate-finance linkages in emerging markets and offers insights for policymakers and financial institutions to integrate environmental risks within supervisory frameworks and risk management strategies to ensure their stability.